Laser triangulation as a fast and reliable method for determining ribbon solid fraction; focus on accuracy, precision, and measurement time - Lillotte, Tim D.; Bebernik, Paul; Keck, Johanna; Bommer, Moritz; Schröder, Daniela; Wagner, Karl G. (International journal of pharmaceutics, 2021)
[Display omitted] •Ribbon solid fraction (SF) via laser triangulation (LT).•Highly accurate and precise analysis of ribbon SF utilizing LT.•LT technique enabling short measurement times.•LT as potential process analytical technology (PAT).•At-line monitoring of roller compaction processes via LT. Roller compaction and dry granulation represent well-established unit operations in the pharmaceutical industry. The ribbon solid fraction is classified as a critical quality attribute, that directly impacts final product quality and performance. The development and evaluation of novel methods measuring ribbon solid fraction represent a subject of current research, since novel analyses strategies need to be established for at-, on–, or in-line process monitoring to overcome limitations of end product testing and to set the course for continuous manufacturing. In this study, a novel analytical device, using the principle of laser triangulation, was investigated to asses its potential being used as at-line process analytical technology tool during a roller compaction process. To this end, the laser triangulation device was compared with X-ray micro-computed tomography and powder based volume displacement measurement techniques using different statistical evaluation methods. Special focus was given to accuracy, precision, and total measurement time. The laser triangulation device was confirmed as highly accurate and precise, enabling the shortest total measurement time compared to the other methods. The findings of this study support the idea of implementing the laser triangulation device as a novel at-line process analytical technology tool into a roller compaction process.